Vegetation diversity, structure and composition of three forest ecosystems in Angsana coastal area, South Kalimantan, Indonesia - YUSANTO NUGROHO; SUYANTO SUYANTO; DINDIN MAKINUDIN; SILVYNA ADITIA; DINDA DEWI YULIMASITA; AHMAD YUSUF AFANDI; MOEHAR MARAGHIY HARAHAP; JERIELS MATATULA; PANDU YUDHA ADI PUTRA WIRABUANA (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Nugroho Y, Suyanto, Makinudin D, Aditia S, Yulimasita DD, Afandi AY, Harahap MM, Matatula J, Wirabuana PYAP. 2022. Vegetation diversity, structure and composition of three forest ecosystems in Angsana coastal area, South Kalimantan, Indonesia. Biodiversitas 23: 2640-2647. Vegetation communities around coastal ecosystems play important roles in mitigating natural disaster and climate change. However, available information about vegetation communities in coastal areas is still limited despite being a requirement in developing strategies for environmental preservation. Angsana coastal area in South Kalimantan, Indonesia has unique characteristics in which it has three different forest ecosystems, namely heath forest (HF), beach forest (BF), and mangrove forest (MF). This study aimed to identify the vegetation diversity, structure and composition of the three forest ecosystems in Angsana coastal area. A field survey was conducted using transect line methods with a sampling plot size of 10 × 10 m and an interval of 20 m. Vegetation communities were assessed using species abundance, plant diversity, importance value index (IVI), and similarity level. Results showed that 37 species from 25 families were recorded at the study site. The highest species abundance was observed in HF (22 species), followed by BF (18 species) and MF (7 species). The same trend was found for vegetation diversity, in which HF had the highest richness (Dmg = 4.52), heterogeneity (H' = 2.86), and evenness (J' = 0.94). Hibiscus tiliaceus L. had the highest IVI in BF in all vegetation stages, and Rhizophora mucronata Lam. consistently had the greatest IVI in MF in all stages. Species thet exhibited the highest IVI in HF were Adina minutiflora Valeton (seedlings), Rhodedomia tomentosa and Premna serratifolia L. (saplings), Tristania maingayi Duthie (poles), and Vitex ovata Thunb. (trees). Our study also observed that species abundance in forest ecosystems gradually declined from seedlings to trees, except in MF. Among the three forest types, vegetation composition was highly similar between MF and BF, with a similarity level of 47.1%. Based on these results, this study concluded that the three forest ecosystems in Angsana coastal area exhibit a highly diverse vegetation structure, and each type of forest has specific characteristics as its entity.